PERAN PENDIDIKAN ISLAM TERHADAP ETIKA POLITIK MAHASISWA FPEB UNIVERSITAS PENDIDIKAN INDONESIA - Agnevia Nursianda; Anatasya Jelita Putri Dirgantara; Livia Anggina; Najwa Ananda Mariana; Riska Anggraeni; Edi Suresman (Cahaya Ilmu Bangsa Institute, 2025)
This study analyzes the role of Islamic education on the political ethics of students of the Faculty of Economics and Business Education (FPEB) of the Indonesian University of Education. Students who receive Islamic education in college are expected to have an ethical political perspective based on Islamic moral values. The purpose of this study is to explore the extent to which Islamic education influences students' attitudes, perceptions, and participation in political activities. The method used in this study is a quantitative survey by distributing questionnaires to FPEB UPI students through a G-form containing closed questions. The results of the study indicate that the majority of students have a good understanding of Islamic education and apply it in their social and political lives. Islamic principles such as honesty, justice, trustworthiness, and deliberation have been proven to play a role in shaping students' political perspectives and behavior. Therefore, with the existence of Islamic education in college, it is hoped that it can create students as a generation that is not only academically intelligent, but also has high moral integrity in their political lives.